2010
DOI: 10.1061/(asce)1090-025x(2010)14:1(47)
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Use of Shredded Tires as Drainage Material in Cover Systems for Abandoned Landfills

Abstract: Over 280 million tires are discarded each year and over 4 billion tires are stockpiled at numerous locations in the United States. The stockpiled tires represent a public health hazard, an aesthetic nuisance, and waste of a valuable resource. Recently, attention has been given to the use of scrap tires for civil engineering applications such as highway embankments, retaining structures, and lightweight fill material. This paper presents the results of a research study performed to assess the feasibility of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Various researchers have carried out investigations on the usage of scrap tire derived materials in civil engineering applications like recycled tire chips as a fill material in road/ embankment construction [6][7][8], lightweight fill material in retaining wall backfill under static loading conditions [2][3][4][5], and waste tire shreds as a leachate collection layer [9,10]. Several researchers [11][12][13][14][15][16][17][18][19][20][21][22] have evaluated the engineering properties of the scrap tire chips and sand tire chip mixtures by conducting permeability, compressibility, large direct shear tests, and triaxial tests on the samples. The permeability and shear strength of the sand tire chip mixtures are higher than that of sand alone [18] and the unit weight of the tire chips is less than one third of that of sand [3] making them fit for light weight fill material.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have carried out investigations on the usage of scrap tire derived materials in civil engineering applications like recycled tire chips as a fill material in road/ embankment construction [6][7][8], lightweight fill material in retaining wall backfill under static loading conditions [2][3][4][5], and waste tire shreds as a leachate collection layer [9,10]. Several researchers [11][12][13][14][15][16][17][18][19][20][21][22] have evaluated the engineering properties of the scrap tire chips and sand tire chip mixtures by conducting permeability, compressibility, large direct shear tests, and triaxial tests on the samples. The permeability and shear strength of the sand tire chip mixtures are higher than that of sand alone [18] and the unit weight of the tire chips is less than one third of that of sand [3] making them fit for light weight fill material.…”
Section: Introductionmentioning
confidence: 99%
“…About 4-5 metric tons of used tires are discarded each year in Jalandhar, Punjab, India (Sethi et al 2013;Kaushik et al 2012). Disposal of the whole tire in landfills or at dump sites may cause an aesthetic nuisance, contamination of the ground, a possible public health hazard, and above all is a wastage of very good resource material (Reddy et al 2010). Waste tire disposal problems may be easily solved by finding alternative methods for reuse of the waste tires in different civil/geotechnical engineering applications.…”
Section: Lcrsmentioning
confidence: 99%
“…In the first experimental sequence, gravel and tire chips were used alone. All tire chips samples were initially characterized by random selection as per the procedure prescribed by Reddy et al (2010). According to Kaushik et al (2012) study tire chips of length 22-28 mm size (aspect ratio 1) demonstrated minimum compressibility and maximum hydraulic conductivity hence, relatively ''free drainage'' even under high overburden pressure levels.…”
Section: Planning and Analysis Of Experimentsmentioning
confidence: 99%
“…Figure 13.1 is a schematic diagram of a typical MCR. Rivero et al (2006) studied MCR for GW treatment under different air velocities, TiO 2 concentrations and permeate fluxes; COD, BOD and turbidity were decreased to 56-98 mg/L (reduction of 67-83%), 2-17 mg/L (87-98%), and 0.35-3.57 NTU (77-98%), respectively. Under the optimal combination of experimental conditions, values of such parameters were 86 mg/L, 9 mg/L, and 0.35 NTU, suggesting that the permeate was reusable.…”
Section: Other Membrane Processesmentioning
confidence: 99%